Sleep duration and cardiometabolic risk: a review of the epidemiologic evidence - Knutson, Kristen L. (2010)
Laboratory studies have found that short-term sleep restriction is associated with impairments in glucose metabolism, appetite regulation and blood pressure regulation. This chapter reviews the epidemiologic evidence for an association between habitual sleep duration and quality and risk of cardiometabolic diseases including obesity, diabetes and hypertension. Multiple studies observed a cross-sectional association between short sleep duration (generally <6 hours per night) and increased body mass index or obesity, prevalent diabetes and prevalent hypertension. Many studies also reported an association between self-reported long sleep duration (generally >8 hours per night) and cardiometabolic disease. There have been a few prospective studies and several, but not all, have found an association between short sleep and incident diabetes, hypertension and markers of cardiovascular disease. Future prospective epidemiologic studies need to include objective measures of sleep, and intervention studies are needed in order to establish a causal link between impaired or insufficient sleep and cardiometabolic disease risk.